Antioxidant and antibacterial activities of red (Hylocereus polyrhizus) and white (Hylocereus undatus) dragon fruits (Journal of Tropical Resources and Sustainable Science (JTRSS), 2022)
Dragon fruit belongs to the genus Hylocereus of the Cactaceae family. There are two species that are commonly cultivated; Hylocerues polyrhizus and Hylocereus undatus that have the same red skin but different flesh colours, red and white respectively. Although from the same genus, the phytochemical contents and bioactivities of both fruits may not be the same. This study aims to compare the phytochemical contents, antioxidant and antibacterial activities of H. polyrhizus and H. undatus to help consumers better choose nutritional fruits and to explore potential natural preservatives. The fruit samples were extracted using 50% ethanol and later were subjected to phytochemical, antioxidant and antibacterial assays. The phytochemical contents were determined using Folin Ciolcalteu and aluminium chloride methods for total phenolic and total flavonoid respectively. The antioxidant activity was determined using diphenyl-picryl hydrazine (DPPH) and 2,2-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) assays. Disk diffusion method was performed to evaluate antibacterial activities against two food-borne pathogens, Escherichia coli and Staphylococcus aureus. H. polyrhizus showed to contain significantly higher phenolic content (p